Вот как это было: повесть / Ю. П. Герман ; худож. О. Фадеева - Герман Юрий Павлович (Вот как это было, 2015)
Экземпляры: ф.8 (20151204) / Инвентарный номер: 52226 / Цена: 243.00. / Сис.шифр: Р2 / Авт.знак: Г 38 / ГРНТИ: 17.82.32 / ББК: 84(2РОс=Рус)6